2007
DOI: 10.1002/chin.200736119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chromans from the Reaction of o‐Quinone Methide Precursor with Substituted Styrenes.

Abstract: The influence of the styrene substituents in the inverse-electron Diels-Alder cycloaddition reaction is discussed. -(BILGIC*, S.; BILGIC, O.; BUEYUEKKIDAN, B.; GUENDUEZ, M.; J. Chem. Res. 2007, 2, 76-79; Dep. Chem., Fac. Arts Sci., Univ. Osmangazi, TR-26480 Eskisehir, Turk.; Eng.) -H. Haber

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Nixon also reported 48 the reaction of cyclic P 3 C 2 t Bu 2 CH(SiMe 3 ) 2 with elemental Se which yields the C/P/Se cage compounds below.…”
Section: Chalcogen-phosphorus Compoundsmentioning
confidence: 96%
“…Nixon also reported 48 the reaction of cyclic P 3 C 2 t Bu 2 CH(SiMe 3 ) 2 with elemental Se which yields the C/P/Se cage compounds below.…”
Section: Chalcogen-phosphorus Compoundsmentioning
confidence: 96%
“…Recently, Bilgic and Mohinder found that o-quinone methide precursor reacted with 1,3-thiazine or substituted styrenes via the Diels-Alder reaction to give chroman derivatives 2a and 2b, 5 On the other hand, 1,2-naphthoquinone-1-methide dimerized to form a spirodimer 3. 6 We also found that o-quinone methide 4 could be prepared from o-dimethylaminomethylphenol or o-methoxymethylphenol (Scheme 1).…”
Section: Figurementioning
confidence: 99%